Contrast versus colour in aposematic signals - Gamberale-Stille, G; Guilford, T (2003)
Conspicuousness is an important feature of warning coloration. One hypothesis for its function is that it increases signal efficacy by facilitating avoidance learning. An alternative, based on the handicap hypothesis, suggests that the degree of conspicuousness holds information directly about the quality of the prey, and that predators associate and learn about the conspicuousness of the coloration, and not the actual colour pattern. We studied the relative importance of signal contrast and the colours of signals for predator attention during discrimination. We used young chicks, Gallus gallus domesticus, as predators and small blue or red paper cones on either matching or contrasting paper backgrounds as stimuli associated with palatable or unpalatable chick crumbs. In four treatment groups, birds could use either cone and/or background colour, cone colour only, background colour only or cone-to-background contrast as cues for discrimination. Only birds in the contrast treatment failed to learn their discrimination task. Birds that had a choice between cone and background colour as cues used the cone colour and they learned the task faster than did birds that had to use background colour as a cue. The results suggest that birds primarily attend to the colours of signals and disregard contrast in discrimination tasks; they thus fail to support a handicap function of conspicuous aposematic coloration. © 2003 Published by Elsevier Science Ltd on behalf of The Association for the Study of Animal Behaviour.